Caminhos para uma educação ambiental crítica como centro de forças no currículo do curso técnico em Mecânica do Ifes/campus Vitória - Deorce, Mariluza Sartori (2014)
This research aimed to conduct a critical analysis of IFES/Vitória Technical Course in order to present ways for the curriculum reorientation, so that environmental education takes the force center in the curriculum. We worked with a qualitative approach, with emphasis on the case study method. The procedures used for data collection were document analysis, semi-structured interviews, focus group and meetings with teachers. The theoretical framework was based on the proposals of Paulo Freire and of authors in the environmental education field, from a critical perspective, in particular, Guimaraes, Lima, Reigota and Loureiro. The analysis moved in permanent tension between regulation and emancipation in order to identify and understand the limitations of the concepts and practices of the course, toward a critical environmental education. These limitations are imposed by the teacher training, the particularities of each discipline, the fragmentation of space /school time, and also by the contradictions inherent to the capitalist system. In the Mechanical technical course, it was found that environmental education is identified with the environmental management of waste and effluents generated in practical activities of laboratories, with the health and safety of the worker and with the organization and cleanliness of the area , although these contents are not explicit in most teaching plans . What happens in the daily school approximates to a conservationist aspect of environmental education, what justified the need to present indications for a curriculum reorientation proposal, that considers environmental education in a critical way and be able to put it as a force center in the curriculum. The ways for the curriculum reorientation, especially by the proposed action of continuing education for teachers, in Freire's perspective, and directions for the construction of the curriculum in a critical direction, may enhance the educational work, from the environmental education with a view to developing a more critical education of Mechanical technical students from IFES/Vitória campus, based on the assumptions of the thought of Paulo Freire